School Culture in Forming the Character of Tolerance in Grade VI Students at SDN 091317 Pematang Raya - Risma Sitohang; Dewi Royani Saragih (Indonesian Journal of Advanced Research, 2023)
This study aims to analyze school culture in the formation of the tolerance character of class VI students at SDN 091317 Pematang Raya, Raya District, Simalungun Regency. This type of research is descriptive analysis with qualitative methods. The determination of research subjects was carried out by purpositive sampling. The research subjects were school principals, teachers and grade VI students. Data collection techniques used are observation, interviews and documentation. Data validity testing technique with source triagulation and method triagulation. The results of the study show that: 1) the formation of the character of tolerance is carried out by the principal and teachers for class VI students, namely through school culture with the policies and school activities that are implemented. 2) Found supporting and inhibiting factors in the formation of the character of tolerance. As supporting factors, namely teacher care, completeness of school facilities, regular communication, and cooperation.